(untitled) (Research, Society and Development, 2023)
Forecasting water demand is fundamental to a region’s social and economic development. In the literature there are several studies with specific applications, However, the topic still lacks a comprehensive view. Therefore, this article proposes a integrative review of the literature, to obtain an overview of the subject (methods, areas of application, objectives, and other factors). Using Methodi Ordinatio methodology, 74 articles with scientific relevance for analysis were selected, most of them published in the USA, Australia, and the United Kingdom. It was concluded that in the use of methods there is a predominance of the approach of artificial neural networks and regression analyzes. As for the application, most studies were for forecasting residential demand.